Adaptive Policing In Asymmetric Conflict: Lessons From Mobile Brigade Regiment Ii In Nduga Regency, Papua, 2018–2025 - Dodi Subrada; Sylvia Prisca Delima; Mohamad Djatmiko (CV Putra Publisher, 2026)
Nduga Regency, Central Papua Province, has become a complex domestic security challenge due to the characteristics of asymmetric conflict, difficult geographical conditions, communication limitations, logistical barriers, and the social dynamics of the local community. This research aims to evaluate the implementation of preventive, repressive, and intelligence strategies in handling KKB during the 2018–2025 period and to formulate an adaptive policing model suited to the context of asymmetric conflict. This research uses a qualitative approach referring to Complex Adaptive Systems theory, Intelligence-Led Policing, the concept of Planning, Organizing, Actuating, and Controlling (POAC), and Community-Oriented Policing. Data were obtained through interviews, study of internal police documents, and secondary data analysis. The results of the research show that handling KKB requires the integration of preemptive, preventive, repressive, and intelligence strategies through the sustained strengthening of Human Intelligence (HUMINT). A repressive approach is needed to deal with the escalation of armed threats, but it needs to be balanced with prevention strategies and community engagement so as not to widen the social distance. The effectiveness of handling is influenced by geographical factors, communication, logistics, organization, personnel quality, as well as support from local government and local figures. This research produces an adaptive policing model that emphasizes response flexibility, integration of intelligence and operational functions, utilization of technology, strengthening of human resources, cross-sector coordination, and continuous evaluation in order to realize an effective and humanistic state presence.